Pengaruh Kompensasi terhadap Kinerja Karyawan Melalui Kepuasan Kerja sebagai Variabel Intervening pada PT. Jambi Ekspres Televisi - Ronaldo Simarmata; Zulfina Adriani; Erwita Dewi (Jurnal Bintang Manajemen, 2025)
This study aims to see the effect of compensation on employee performance through job satisfaction as an intervening variable at PT Jambi Ekspres Televisi. The technique applied for this study is quantitative research. The population for this study was all employees of PT Jambi Ekspres Televisi as many as 30 people and for the research sample as many as 30 people. The data collection method used was a questionnaire that had been proven valid and reliable. The research analysis method used descriptive statistical analysis using the equation model structure (SEM), with Smart PLS 4.0 Software as a tool to process the data. The output of this study shows that compensation has a positive and significant effect on employee performance, compensation has a positive and significant effect on employee job satisfaction, job satisfaction has a positive and significant effect on employee performance, compensation has a positive and significant effect on employee performance through job satisfaction as an intervening variable.